Automatic scheduling using Forward Chaining for Ethics Protocol Review - Ratih Nur Esti Anggraini; Azzam Jihad Ulhaq; M. Syauqi Hanif Ardani (Sistemasi: Jurnal Sistem Informasi, 2023)
Research involving humans as the object has to follow ethics protocol. This protocol has to be reviewed by the research ethics committee before the research can be conducted. Though the mechanism for determining the protocol reviewer is simple, there are several obstacles, including the unbalanced workload of each reviewer, the empty schedule because the reviewer is busy or has other tasks, and the length of time it takes to determine the schedule manually. There needs to be a system that can see various obstacles and challenges in scheduling protocol reviewers and resolve them automatically. This paper proposes an automatic scheduling mechanism with a Heuristic Forward Chaining approach that can adjust the rules for determining reviewers from real experts and avoid the constraints that exist in the manual scheduling system. The proposed method is made in the form of a web application and can practically generate accurate schedules automatically.